2 PROBLEM OF PRESERVATION OF ARCHITECTURAL MONUMENTS OF OLD MOSCOW AS VIEWED BY ITS RESIDENTS - Savitskaya Anastasiya Valer'evna; Chistova Anastasiya Evgen'evna; Pryadko Igor' Petrovich (Stroitel’stvo: Nauka i Obrazovanie, 2015)
The authors consider one of the most relevant issues of the present-day urban planning, the issue of preservation of the historic environment, the architectural and urban planning space of the megalopolis in the context of the accelerated pace of urbanization, expansion of the capital in the course of its implementation. The authors argue that the problem considered in the paper is not easy to tackle. The point is that the need to preserve historic built-up areas is hardly reconcilable with the need to upgrade the urban infrastructure. A social conflict is inevitable in this context. The authors track development of this social conflict from the sixties of the 20ieth century and through the present time and provide their resolutions to this contradiction.